Multimodal electrophysiological studies including motor evoked potentials in patients with locked-in syndrome: report of six patients. Issue 11 (November 1994) - Bassetti, C; Mathis, J; Hess, C W
Abstract : Clinical and electrophysiological findings in six patients with locked-in syndrome are reported. Motor evoked potentials (MEPs) after magnetic stimulation of the motor cortex were absent in four patients, none of whom recovered clinically. In two patients, MEPs could be obtained from the severely paretic limbs and almost full motor recovery followed. Somatosensory evoked potentials were altered in four of the patients, and brainstem auditory evoked potentials were altered in two of four patients examined, showing a clinically unsuspected tegmental involvement. The EEG showed a predominance of reactive alpha activity in all patients, documenting a preserved consciousness. It is concluded that a multimodal electrophysiological approach, in addition to clinical assessment, can be helpful in diagnosing locked-in syndrome, estimating the extension of the underlying brainstem dysfunction, and predicting functional outcome.